Creating Temporally Dynamic Web Search Snippets - Svore, Krysta M.; Teevan, Jaime; Dumais, Susan; Kulkarni, Anagha (Proceedings of SIGIR'12, Portland, Oregon, USA, 2012)
Content on the Internet is always changing. We explore the value of biasing search result snippets towards new webpage content. We present results from a user study comparing traditional query-focused snippets with snippets that emphasize new page content for two query types: general and trending. Our results indicate that searchers prefer the inclusion of temporal information for trending queries but not for general queries, and that this is particularly valuable for pages that have not been recently crawled.